Black soldier fly larvae (BSFL) and their affinity for organic waste processing - Siddiqui, Shahida Anusha; Ristow, Bridget; Rahayu, Teguh; Putra, Nugroho Susetya; Yuwono, Nasih Widya; Nisa', Khoirun; Mategeko, Bosco; Smetana, Sergiy; Saki, Morteza; Nawaz, Asad; Nagdalian, Andrey (Elsevier, 2022)
There are two major problems that we are facing currently. Firstly, a growing human population continues to contribute to the increased food demand. Secondly, the volume of organic waste produced will threaten human health and the quality of the environment. Recently, there is an increasing number of efforts placed into farming insect biomass to produce alternative feed ingredients. Black soldier fly larvae (BSFL), Hermetia illucens have proven to convert organic waste into high-quality nutrients for pet foods, fish and poultry feeds, as well as residue fertilizer for soil amendment. However, better BSFL feed formulation and feeding approaches are necessary for yielding a higher nutrient content of the insect body, and if performed efficiently, whilst converting waste into higher value biomass. Lastly, this paper reveals that BSFL, in fact, thrives in various ranges of organic matter composition and with simple rearing systems.